An Atlas of the Arabic Language: Importance, Perceptions and Steps to Achievement - ben guesmia, rachid (El Omda in Linguistics and Discourse Analysis, 2023)
linguistic atlases in the Arab world is still in its infancy. Accordingly, the study attempted to answer a number of questions summarized as follows: Do we need an atlas of the Arabic tongue? What is the significance of his civilizational achievement? What is its strategic rationale? How do we implement this project? What are the working groups? What are its scientific sources? What are his steps of achievement? In answering the previous problem, the study adopted a methodology that divided the research into three main axes. The first dealt with geographical linguistics, while the second was to talk about linguistic atlases and their manufacture, and the third axes presented a set of perceptions about the project of achieving an atlas of the Arabic tongue, its measures, its sources, and its implemen